THE RELATIONSHIP BETWEEN ANONYMITY AND CYBER SEXUAL HARASSMENT BY TWITTER USERS: A CROSS-SECTIONAL STUDY - Rosemary, Rizanna; Wardhana, Arief Bayu; Syam, Hamdani M.; Susilawati, Novi (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2024)
Background: Cases of cyber sexual harassment are increasing, especially during the Covid-19 pandemic. SAFEnet data showed cases of online sexual harassment and in 2020 increased by 40%, namely 659 cases. Purpose: This cross-sectional study aimed to determine the relationship between anonymity and Twitter users' desire to commit cyber sexual harassment and test the Deindividuation theory. Methods: The population in this study were Twitter users aged 16-54 years. The sample size was determined using the Slovin formula with a sample of 280 respondents, who were selected randomly. Data collection through questionnaire distribution, using the Sexual Experiences Questionnaire (SEQ) scale. Results: Through data analysis with SPSS 25.0, it was found that the Pearson Product Moment correlation value between anonymity and Cyber Sexual Harassment (CSH) was (r) 0.749 > r_table 0.113. Conclusion: The research shows that there is a relationship between anonymity and Twitter users' willingness to commit cyber sexual harassment, with a positive relationship direction. The lower the anonymity, the lower the desire to commit CSH, and vice versa. Abstrak Latar Belakang: Kasus pelecehan seksual siber meningkat terkhusus di masa pandemi Covid-19. Data SAFEnet menunjukkan kasus pelecehan seksual secara online dan pada tahun 2020 meningkat 40%, yakni 659 Kasus. Tujuan: Studi cross-sectional ini bertujuan untuk mengetahui hubungan anonimitas dengan keinginan pengguna Twitter melakukan pelecehan seksual siber dan menguji teori Deindividuasi. Metode: Populasi pada penelitian ini adalah pengguna Twitter usia 16-54 tahun. Jumlah sampel ditentukan dengan rumus Slovin dengan sampel sebanyak 280 responden, yang dipilih secara acak (random). Pengumpulan data melalui penyebaran kuesioner, dengan menggunakan skala Sexual Experiences Questionnaire (SEQ). Hasil: Melalui analisis data dengan SPSS 25.0, ditemukan bahwa nilai korelasi Pearson Product Moment antara anonimitas dengan Cyber Sexual Harassment (CSH) adalah (r) 0,749 > r_tabel0,113. Kesimpulan: Penelitian menunjukkan terdapat hubungan antara anonimitas dengan keinginan pengguna Twitter melakukan pelecehan seksual siber, dengan arah hubungan yang positif. Semakin rendah anonimitas, semakin rendah keinginan untuk melakukan CSH, dan sebaliknya.